Meningkatkan Motivasi Belajar IPA Peserta Didik melalui Project Based Learning Pasca Pandemi Covid-19 di Kelas VI.C SDN 04 Payakumbuh T.P 2021/2022 - Zuharnelhas Zuharnelhas (Journal on Education, 2022)
Science learning is a learning content that is favored by students. Because the material is directly related to everyday life. Online learning causes students' interest to decrease in learning. So that the IPA load value obtained is low. So it is hoped that the Project Based Learning model can help improve student learning outcomes in science learning content. The implementation of the Project Based Learning model consists of five activities, namely: determining fundamental questions, designing project plans, compiling schedules, monitoring students and project progress, testing results, evaluating experiences, product finalization and publication. The data obtained comes from the data of students, teachers, and documentation. Data collection procedures used observation instruments, field notes, tests, observations of collaborators and documentation. We can see the results obtained from three sides. The first is from the implementation side which relates to students' interest in carrying out learning which shows an increase, secondly the character formation of students is reflected from the assignment assignments, and thirdly, there is an increase in students' natural science learning outcomes with the Project Based Learning model in class VI.C SD Negeri 04 Payakumbuh.